Missing growth measurement in Germany - Vanessa Schmidt; Sven Schreiber (ZBW - Leibniz Information Centre for Economics, 2020)
Using detailed establishment-level micro data, this paper analyzes the quantitative implications of the missing-growth hypothesis by Aghion, Bergeaud, Boppart, Klenow, and Li (2019) for Germany. This hypothesis states that actual growth rates of real output are systematically understated by official estimates, such that a part of real growth is missing in the published data. The underlying effect rests on overstated inflation estimates due to imputed prices for disappearing goods and services varieties, which is indirectly measured by plant entry and exit dynamics. Using different market share proxies our main results regarding understated real output growth lie in the range of 0:39 to 0:54 percentage points per year on average for the benchmark sample 1998-2016. These are quite closely in line with existing findings for France, the USA, and Japan (in different periods). We provide additional robustness analysis and discuss limitations of the approach.
Keywords: E31; O47; 330; creative destruction; price imputation; inflation measurement